Down-regulation of 11β-hydroxysteroid dehydrogenase type 2 by bortezomib sensitizes Jurkat leukemia T cells against glucocorticoid-induced apoptosis. - Yi Tao (Public Library of Science (PLoS), 2013)
11β-Hydroxysteroid dehydrogenases type 2 (11β-HSD2), a key regulator for pre-receptor metabolism of glucocorticoids (GCs) by converting active GC, cortisol, to inactive cortisone, has been shown to be present in a variety of tumors. But its expression and roles have rarely been discussed in hematological malignancies. Proteasome inhibitor bortezomib has been shown to not only possess antitumor effects but also potentiate the activity of other chemotherapeutics. In this study, we demonstrated that 11β-HSD2 was highly expressed in two GC-resistant T-cell leukemic cell lines Jurkat and Molt4. In contrast, no 11β-HSD2 expression was found in two GC-sensitive non-hodgkin lymphoma cell lines Daudi and Raji as well as normal peripheral blood T cells. Inhibition of 11β-HSD2 by 11β-HSD inhibitor 18β-glycyrrhetinic acid or 11β-HSD2 shRNA significantly increased cortisol-induced apoptosis in Jurkat cells. Additionally, pretreatment of Jurkat cells with low-dose bortezomib resulted in increased cellular sensitivity to GC as shown by elevated induction of apoptosis, more cells arrested at G1 stage and up-regulation of GC-induced leucine zipper which is an important mediator of GC action. Furthermore, we clarified that bortezomib could dose-dependently inhibit 11β-HSD2 messenger RNA and protein levels as well as activity (cortisol-cortisone conversion) through p38 mitogen-activated protein kinase signaling pathway. Therefore, we suggest 11β-HSD2 is, at least partially if not all, responsible for impaired GC suppression in Jurkat cells and also indicate a novel mechanism by which proteasome inhibitor bortezomib may influence GC action.